2016
DOI: 10.1038/srep22640
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA MALAT1 promotes hepatic steatosis and insulin resistance by increasing nuclear SREBP-1c protein stability

Abstract: Metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) is implicated in liver cell proliferation. However, its role in hepatic steatosis and insulin resistance remain poorly understood. The aim of this study was to investigate the effects of MALAT1 on hepatic lipid accumulation and its potential targets. As expected, MALAT1 expression is increased in hepatocytes exposed to palmitate and livers of ob/ob mice. Knockdown of MALAT1 expression dramatically suppressed palmitate-induced lipid accumulation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
164
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(173 citation statements)
references
References 31 publications
8
164
1
Order By: Relevance
“…Another lncRNA, Alu -mediated p21 transcriptional regulator ( APTR ), was found to be upregulated in human cirrhosis and activated hepatic stellate cells [32]. Expression of metastasis-associated lung adenocarcinoma transcript 1 ( MALAT1 ) was increased in livers of ob/ob mice, as well as hepatocytes exposed to palmitate [33]. These investigations of single lncRNAs provide a further rationale for the analysis of global changes in lncRNA expression in NAFLD and NASH.…”
Section: Introductionmentioning
confidence: 99%
“…Another lncRNA, Alu -mediated p21 transcriptional regulator ( APTR ), was found to be upregulated in human cirrhosis and activated hepatic stellate cells [32]. Expression of metastasis-associated lung adenocarcinoma transcript 1 ( MALAT1 ) was increased in livers of ob/ob mice, as well as hepatocytes exposed to palmitate [33]. These investigations of single lncRNAs provide a further rationale for the analysis of global changes in lncRNA expression in NAFLD and NASH.…”
Section: Introductionmentioning
confidence: 99%
“…MALAT1 induced hepatic lipid accumulation and insulin resistance by interacting with SREBP-1c and stabilizing its protein in hepatocytes. 28 Knockdown of MALAT1 effectively reversed lipid aggregation and increased insulin sensitivity in ob/ob mice.…”
Section: Lncrnas In Hepatic Lipid and Glucose Metabolismmentioning
confidence: 93%
“…For example, LncLGRAs, the transcriptional regulatory factor of the hepatic GCK gene, can inhibit the expression of GCK and reduce hepatic glycogen content in mice during fasting [55]. Enhanced expression of lncRNA MALAT1 either in vivo or in vitro activates nuclear SREBP1c expression and induces its intracellular lipid accumulation in mouse hepatocytes [56]. Our previous studies have indicated that significant differentially expressed mRNAs and miRNAs in peak-laying chickens are highly relevant to hepatic lipid metabolism [27,36].…”
Section: Discussionmentioning
confidence: 99%